Concepts of Modern Social and Moral Education in the Kingdom of Poland at the Turn of the 19th and 20th Centuries - Aneta Bołdyrew; Joanna Falkowska (Lubelski Rocznik Pedagogiczny, 2022)
Introduction: Modernisation transformations within the Polish lands at the end of the 19th and the beginning of the 20th century were linked to the development and popularisation of scientific pedagogy and the growing importance of children and youth in social life. The postulates of universal education were connected with the need to develop concepts of upbringing, corresponding to the requirements of modern reality, in Polish realities, which was also a period of irredentist aspirations.